Small Molecules in Parkinson’s Disease Therapy: From Dopamine Pathways to New Emerging Targets - Hwayoung Lee; Ahmed Elkamhawy; Polina Rakhalskaya; Qili Lu; Hossam Nada; Guofeng Quan; Kyeong Lee (Pharmaceuticals)
Parkinson’s disease (PD) is a chronic, progressive neurological disorder affecting approximately 10 million people worldwide, with prevalence expected to rise as the global population ages. It is characterized by the degeneration of dopamine-producing neurons in the substantia nigra pars compacta, leading to motor symptoms such as tremor, rigidity, bradykinesia, postural instability, and gait disturbances, as well as non-motor symptoms including olfactory disturbances, sleep disorders, and depression. Currently, no cure exists for PD, and most available therapies focus on symptom alleviation. This dopamine deficiency impairs motor control, and since dopamine itself cannot cross the blood–brain barrier (BBB), the precursor L-Dopa is commonly used in treatment. L-Dopa is administered with enzyme inhibitors to prevent premature conversion outside the brain, allowing it to cross the BBB and convert to dopamine within the central nervous system. Although these therapies have improved symptom management, recent research has revealed additional molecular factors in PD pathology, such as α-synuclein aggregation, mitochondrial dysfunction, and lysosomal abnormalities, contributing to its complexity. These discoveries open up possibilities for neuroprotective therapies that could slow disease progression. In this review, we categorize PD therapeutic targets into two main groups: currently used therapies and targets under active research. We also introduce promising small-molecule compounds studied between 2019 and 2023, which may represent future treatment options. By examining both established and emerging targets, we aim to highlight effective strategies and potential directions for future drug development in Parkinson’s disease therapy.